The Influence of Ethical Leadership and Knowledge Sharing on Employee Performance Mediated with Higher College Commitment - Harjono, La; Nurcholis, Lutfi; Khajar, Ibnu; Mulyana, Mulyana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study aims to investigate the relationship between ethical leadership and knowledge sharing on employee performance mediated by organizational commitment at Muhammadiyah Ponorogo universities using the SMART PLS 4 method. The population in this study is staff at Muhammadiyah Ponorogo University using non-probability sampling techniques using a purposive approach. sampling with a sample size of 100 people according to the criteria. The results show that Ethical Leadership has a positive and significant effect on Organizational Commitment, and Knowledge Sharing also has a positive and significant impact on Organizational Commitment, Ethical Leadership has a positive and significant effect on employee performance, but Knowledge Sharing has no positive impact on employee performance, Organizational Commitment has a positive effect on performance employee.